Differences in Sociodemographic Correlates of Human Papillomavirus-Associated Cancer Survival in the United States. (14th October 2021) - Osazuwa-Peters, Nosayaba; Simpson, Matthew C.; Rohde, Rebecca L.; Challapalli, Sai D; Massa, Sean T.; Adjei Boakye, Eric
Objectives: Human papillomavirus (HPV)-associated cancers account for about 9% of the cancer mortality burden in the United States; however, survival differs among sociodemographic factors. We determine sociodemographic and clinical variables associated with HPV-associated cancer survival. Methods: Data derived from the Surveillance, Epidemiology, and End Results 18 cancer registry were analyzed for a cohort of adult patients diagnosed with a first primary HPV-associated cancer (anal, cervical, oropharyngeal, penile, vaginal, and vulvar cancers), between 2007 and 2015. Multivariable Fine and Gray proportional hazards regression models stratified by anatomic site estimated the association of sociodemographic and clinical variables and cancer-specific survival. Results: A total of 77 774 adults were included (11 216 anal, 27 098 cervical, 30 451 oropharyngeal, 2221 penile, 1176 vaginal, 5612 vulvar; average age = 57.2 years). The most common HPV-associated cancer was cervical carcinoma (58%) for females and oropharyngeal (81%) for male. Among patients diagnosed with anal/rectal squamous cell carcinoma (SCC), males had a higher risk of death than females. NonHispanic (NH) blacks had a higher risk of death from anal/rectal SCC, oropharyngeal SCC, and cervical carcinoma; and Hispanics had a higher risk of death from oropharyngeal SCC than NH whites. Marital status was associated with risk of death for all anatomic sites except vulvar. Compared to nonMedicaid insurance, patients with Medicaid and uninsured had higher risk of death from anal/rectal SCC, oropharyngeal SCC, and cervical carcinoma. Conclusions: There exists gender (anal) and racial and insurance (anal, cervical, and oropharyngeal) disparities in relative survival. Concerted efforts are needed to increase and sustain progress made in HPV vaccine uptake among these specific patient subgroups, to reduce cancer incidence.